The Emerald International Handbook of Technology-Facilitated Violence and Abuse 2021
DOI: 10.1108/978-1-83982-848-520211052
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Apathy and Intervention in the Era of Social Media

Abstract: Bystander apathy has been a source of debate for decades. In the past halfcentury, psychologists developed theoretical frameworks to understand bystander activity, commonly referred to as bystander intervention models (BIMs). More recently, BIMs have been modified to facilitate initiatives to prevent various forms of online victimization. This chapter begins with a review of BIMs and recent applications of bystander intervention research to online environments. We also present several future directions for res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…In addition, a clear message emerged that bystander intervention to this behaviour was a moral responsibility, even if this did not impact on the male perpetrator and female victim directly; this could have a wider social good of supporting others to report coercive control. This study replicated other research suggesting that victims of online harassment may have social support online (Lytle, 2021). However, the findings were also compatible with Models of Bystander Intervention (Latané and Darley, 1970) which suggest people experience internal conflict witnessing “wrong” behaviour but factors such as proximity to the victim (Palmer et al , 2018) or if the victim is unknown to the witness with a large number of bystanders; this may also diffuse responsibility (Butler et al , 2022) .…”
Section: Resultssupporting
confidence: 89%
“…In addition, a clear message emerged that bystander intervention to this behaviour was a moral responsibility, even if this did not impact on the male perpetrator and female victim directly; this could have a wider social good of supporting others to report coercive control. This study replicated other research suggesting that victims of online harassment may have social support online (Lytle, 2021). However, the findings were also compatible with Models of Bystander Intervention (Latané and Darley, 1970) which suggest people experience internal conflict witnessing “wrong” behaviour but factors such as proximity to the victim (Palmer et al , 2018) or if the victim is unknown to the witness with a large number of bystanders; this may also diffuse responsibility (Butler et al , 2022) .…”
Section: Resultssupporting
confidence: 89%
“…In addition to the alternative responses described above, creating holistic responses to TFVB will also require alternative bodies to work to enact systems-level changes and to challenge the culture that normalizes TFVB. For instance, comprehensive educational initiatives 8 could both challenge discriminatory beliefs related to TFVB, such as homophobic, racist, or sexist beliefs that often underly acts of TFVB (Henry et al, 2017; Mishna and Van Wert, 2015), and teach bystanders how to support victims or positively intervene in acts of TFVB (Albury et al, 2017; Lytle et al, 2021; Powell and Henry, 2017). As I argue elsewhere (Dodge, 2021a, 2021b), robust public education could be paired with an holistic restorative approach to address the myriad failures, on the part of individuals, community, culture, and systems, that create and invigorate the harms of TFVB.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the degree to which, if at all, an online bystander will defend a victim can be predicted by her or his social group, attitudes and situational influences (Lytle et al 2021).…”
Section: The Role Of Bystanders In Aggravating Perpetuating and Mitig...mentioning
confidence: 99%